Nicotinic Restoration of Excitatory Neuroplasticity Is Linked to Improved Implicit Motor Learning Skills in Deprived Smokers - Grundey, Jessica; Thirugnasambandam, Nivethida; Amu, Rosa; Paulus, Walter; Nitsche, Michael A. (Frontiers in Neurology, 2018)
Nicotine has been shown to modulate neuroplasticity, cognition and learning processes in smokers and non-smokers. A possible mechanism for its effect on learning and memory formation is its impact on long-term depression (LTD) and long-term potentiation (LTP). Nicotine abstinence in smokers is often correlated with impaired cognitive performance. As neuroplasticity is closely connected to learning and memory formation, we aimed to explore the effect of nicotine spray administration in deprived smokers on paired-associative stimulation (PAS25)-induced neuroplasticity and on performance of the serial reaction time task (SRTT), a sequential motor learning paradigm. Deprived smokers (n=12) under placebo medication displayed reduced excitatory neuroplasticity induced by PAS25. Plasticity was restored by nicotine spray administration. Likewise, SRTT-performance improved after nicotine spray administration compared to placebo administration (n=19). The results indicate a restitutional effect of nicotine spray in deprived smokers on both: Long-term potentiation-like neuroplasticity and motor learning. These results present a possible explanation for persistence of nicotine addiction and probability of relapse.